Team sport athletes` perceptions and use of recovery strategies: a mixed-methods survey study - Crowther, F.; Sealey, R.; Crowe, M.; Edwards, A.; Halson, S. (BMC Sports Science, Medicine and Rehabilitation, 2017)
Background